Modelagem e mapas de capacidade suporte de carga de solos cultivados com cana-de-açúcar - Miranda, Elka Élice Vasco de [UNESP] (Universidade Estadual Paulista (Unesp), 2006)
New studies must consider and quantify the load level that a determined soil can receive and in what management condition this soil can be handled without suffering physical alterations and additional compaction. The objectives of this work were to quantify the preconsolidation pressure, suggesting it as a quantitative indicator of the soil structural sustentabilidade cultivated with sugar cane; to get models that allow to predict the behavior of the soil structure cultivated with sugar cane in function of the preconsolidation pressure and the water content; to get agricultural traffic maps in function of water content and the preconsolidation pressure of the soil using geostatistics resources; and to evaluate the soil mechanical resistance, based on cone index and water content variation under several types of soils. Soil samples from several soil classes were collected cropped with sugar cane and areas that varied from 4.88 and 17.86 ha. The maps that illustrated the spatial variability of the several physical attributes were made using statistical and geostatistical resources. The models of the soil load capacity satisfactory modeled the behavior of the soil structure in function of the water content and depth, helping the maximum load prediction that this soil can receive without compromising its structure. The obtained models were sensible to identify the consolidation structure, identifying the layers and grids with huge mechanical resistance. The use of geostatistical tools and mapping the studied attributes showed a promising tool to take decisions about the system, aiming at, over all the soil structure sustentation. The maps of the soil load capacity constituted an efficient tool to locate 4 areas into the field with compromised structure, making possible to plan the correct dimension of the machinery... (Complete abstract, click electronic access below)
Keywords: Agricultura de precisão; Solos - Compactação; Mecanização; Agricultura - Mapas; Cana-de-açúcar; Soil compactation; Load capacity maps; Precision farming